PENGARUH PERFORMANCE-ENHANCING, FUNCTIONALITY, HEDONIC CONTENT, SOCIAL CONTENT DAN FLOW EXPERIENCE TERHADAP PURCHASE INTENTION MELALUI AFFECTIVE ONLINE IMPULSE BUYING TENDENCY PADA GAME VALORANT - Devando Darren Wijaya; andreas kiky (Jurnal Nusa Manajemen, 2026)
The growth of microtransactions in competitive games such as Valorant has encouraged more spontaneous purchasing behavior, especially when players are deeply engaged in gameplay. This study aims to examine the effects of performance-enhancing, functionality, hedonic content, social content, and flow experience on Affective Online Impulse Buying Tendency (IBT) and its impact on purchase intention among Valorant players. A quantitative approach was employed by collecting data through an online questionnaire from approximately 150 Valorant players, and the data were analyzed using PLS-SEM with SmartPLS 4. The results show affective online impulse buying tendency has a positive and significant effect on purchase intention. The indirect effect test indicates that only flow experience exerts a positive and significant indirect effect on purchase intention through affective online impulse buying tendency. In conclusion, flow experience is the key factor that increases affective impulse buying tendency, which subsequently strengthens players’ intention to purchase microtransactions in Valorant.